(untitled) (The International Journal for Scientific Research, 2023)
The aim of this paper is to illustrate the Egwaider type-II (EGW-II) distribution as a new discrete probability distribution that may will have some practical applications in life. The EGW-II distribution is a discrete probability distribution generated as another special case of the finite Egwaider distribution. The properties of this discrete distribution are discussed. Some special cases from the distribution are introduced and some remarks about it are given. Data from this discrete distribution are simulated and used to estimate its shape parameter using two methods of estimation, namely, the maximum likelihood method of estimation and the moments method of estimation. Finally, the conclusion and discussion are given.